Associations between peripheral nerve stimulation and cognitive performance: insights from healthy individuals and various disease pathologies - Liu, Xing; Yang, Chenyi; Wang, Xinyi; Wang, Zixuan; Liao, Huihui; Liu, Huan; Zhang, Miao; Zhang, Lin; Wang, Haiyun (Frontiers in Aging Neuroscience, 2025)
Cognitive dysfunction can manifest as declines in memory, learning, and attention, stemming from multifaceted factors. Risk factors encompass a spectrum including genetics, lifestyle choices, and personal medical history. Conditions such as Alzheimer’s disease (AD), depression, epilepsy, and exposure to surgical/anesthesia may correlate with cognitive impairment. Recent advancements in nerve stimulation techniques indicate significant potential for enhancing cognitive function. Understanding the mechanisms of peripheral nerve stimulation (PNS) can improve the management of cognitive impairment and promote its clinical application, advancing cognitive rehabilitation for patients. Following a comprehensive search and selection process, we finally included 47 studies that examined the effects of PNS on cognitive performances of both healthy individuals and various disease pathologies. The aggregated findings suggest that PNS influences crucial brain pathways, such as the ganglia and nucleus tractus solitarius, which project to areas essential for memory consolidation, including the hippocampus and amygdala. PNS improves cognitive function through mechanisms such as neurotransmitter modulation and neuronal activity regulation. However, the effects of PNS on cognitive function vary depending on the pathological condition. Additionally, the efficacy of PNS is influenced by both the intensity and pattern of stimulation. In summary, PNS appears to be a promising modality for enhancing cognitive function, particularly in neurological disorders such as AD and epilepsy. While further research is needed to fully elucidate the mechanisms, current evidence suggests that PNS could offer a valuable therapeutic option for improving memory and attention. With its potential for broad application and non-invasive nature, PNS represents an exciting avenue for future research and clinical practice in cognitive enhancement.